2023
DOI: 10.1186/s13058-023-01631-6
|View full text |Cite
|
Sign up to set email alerts
|

Serum immuno-oncology markers carry independent prognostic information in patients with newly diagnosed metastatic breast cancer, from a prospective observational study

Abstract: Background Metastatic breast cancer (MBC) is a challenging disease, and despite new therapies, prognosis is still poor for a majority of patients. There is a clinical need for improved prognostication where immuno-oncology markers can provide important information. The aim of this study was to evaluate serum immuno-oncology markers in MBC patients and their respective relevance for prediction of survival. Patients and methods We investigated a bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…FASLG is expressed on cytotoxic T cells, where it is an inducer of apoptosis through its binding with the Fas receptor [32]. Previous studies have found an association between FASLG expression and anti-cancer activity [33,34]. A recent study by Gunnarsdottir et al using Olink PEA showed an association between high serum FASLG levels and improved OS and PFS rates in breast cancer [34], which is similar to the results shown in this study.…”
Section: Discussionsupporting
confidence: 90%
“…FASLG is expressed on cytotoxic T cells, where it is an inducer of apoptosis through its binding with the Fas receptor [32]. Previous studies have found an association between FASLG expression and anti-cancer activity [33,34]. A recent study by Gunnarsdottir et al using Olink PEA showed an association between high serum FASLG levels and improved OS and PFS rates in breast cancer [34], which is similar to the results shown in this study.…”
Section: Discussionsupporting
confidence: 90%
“…Another protein of the IL family included in the prognostic model was IL-10, a pleiotropic inflammatory and immune system regulator, which was only one of the nine identified proteins in the signature that predicted improved outcome [ 27 ]. Recently, high PEA-measured IL-10 levels were reported to be associated with worse progression-free survival in metastatic breast cancer [ 28 ]. In line with our results, high tissue expression of IL-10 was associated with improved DFS and BCSS in a series of 1380 early breast cancer patients in univariate analysis [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…IL-6 is a major regulator of myeloid-derived suppressor cells (MDSCs) that suppress the anti-tumour functions of T and NK-cells. High plasma IL-6 is therefore associated with a worse prognosis as it leads to increased tumour cell proliferation and metastasis [ 45 47 ]. Additionally, more extensive surgical trauma and sympathetic activation during mastectomy may cause greater adrenergic and prostaglandin responses, which also affect immune function.…”
Section: Discussionmentioning
confidence: 99%